The Portuguese rainbow: LGBTQI+ rights and experiences - Saleiro, S. P. (Portuguese Journal of Social Science, 2021)
Portugal has made a remarkable progress in promoting the rights of Lesbian, Gay, Bisexual, Trans, Queer and Intersex (LGBTQI+) people since the turn of the century. However, the knowledge produced in social science on the experiences of LGBTQI+ people in Portugal demonstrate the shortcomings and challenges of the transition from legal rights to lived experience. This issue is built around the rights as they relate to sexual orientation, gender identity and expression and sexual characteristics and to the experiences of LGBTQI+ people in Portugal, contextualized at the European and international level. The issue includes articles that, taken as a whole, provide domestic and international reader’s critical knowledge about the LGBTQI+ community and lives in Portugal by the hand of some of the country’s leading scholars in this area.